2005
DOI: 10.1002/dvdy.20651
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid cooperates with EGF in inducing branching morphogenesis of embryonic mouse salivary epithelium

Abstract: Epithelial morphogenesis is supported by diffusible growth factors and by nondiffusible cell substrata, such as laminin and fibronectin. When embedded in a laminin-rich basement-membrane substratum, embryonic mouse submandibular epithelium undergoes cell proliferation and branching morphogenesis in response to epidermal growth factor (EGF) in mesenchyme-free culture but not in serum-free medium. In this study, we sought to identify the biologically active factor in serum. As this factor was heat-stable and try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In previous reports, serum was required for tissue interactions between the salivary epithelium and mesenchyme [123,124]. The supplementation of serum is beneficial to salivary morphogenesis because it provides many essential factors [125]. However, for tissue regeneration, the addition of serum might be costly and impair biocompatibility.…”
Section: Applicationsmentioning
confidence: 99%
“…In previous reports, serum was required for tissue interactions between the salivary epithelium and mesenchyme [123,124]. The supplementation of serum is beneficial to salivary morphogenesis because it provides many essential factors [125]. However, for tissue regeneration, the addition of serum might be costly and impair biocompatibility.…”
Section: Applicationsmentioning
confidence: 99%
“…The mechanisms through which clefts initiate remain unclear but mesenchymally-induced activation of autocrine EGF signaling in the epithelium appears to promote cleft initiation [26], and lysophosphatidic acid (LPA) can synergize with EGF [27] (Figure 2). Semaphorin 3A/3C acting through the neuropilin receptor 1 (Nrp1) [28] may also be involved.…”
Section: How Is Cleft Formation Coordinated?mentioning
confidence: 99%
“…We reported previously that addition of LPA to EGF-supplemented medium dramatically enhanced branching morphogenesis of the SMG epithelium cultured in Matrigel (Noguchi et al, 2006), but there was no confirmation that LPA had similar effects in combination with other EGF family growth factors. To confirm branching morphogenesis, TGFa, HBEGF, and NRG1, excluding AREG and EREG whose gene expressions were negligible in the epithelium, were tested.…”
Section: Effects Of Lpa On Branching Morphogenesis Induced By Egf Fammentioning
confidence: 99%
“…Growth factors play important roles in the developmental processes of the mouse submandibular gland (SMG). Epithelium‐alone culture studies, in which the mesenchyme‐free SMG epithelium was embedded in basement membrane‐like substratum (Matrigel), revealed that epidermal growth factor (EGF) extensively induced branching morphogenesis of the epithelium in the presence of serum or lysophosphatidic acid (LPA) (Nogawa and Takahashi, ; Noguchi et al, ). Among EGF family members, EGF, transforming growth factor α (TGFα), heparin‐binding EGF (HBEGF), and neuregulin 1 (NRG1) were reported to be expressed in developing SMG in vivo, and the expressions of EGF receptors were also confirmed in developing SMG (Gresik et al, ; Kashimata and Gresik, ; Jaskoll and Melnick, ; Umeda et al, ; Miyazaki et al, ; Nitta et al, ).…”
Section: Introductionmentioning
confidence: 99%